Temperature and Humidity Monitoring System Using Node-Red Based on MQTT Protocol - Utomo, Eko Budi; Izzaturrahmani, Nurhaliza (Journal of Electrical Engineering and Computer (JEECOM), 2025)
Temperature and humidity monitoring system integrated with the Internet of Things (IoT) is an innovative step in monitoring environmental conditions in real-time. This research develops a monitoring system based on the MQTT (Message Queuing Telemetry Transport) protocol integrated with the Node-RED platform. A temperature sensor is used to read temperature data, which is then sent via the MQTT protocol to the broker server. Node-RED acts as a visual interface to process, analyze, and display the temperature data in the form of an interactive dashboard. The system is designed to support easy integration, lightweight data management, and remote monitoring. Experimental data was obtained by comparing sensor readings with a variety of different environmental conditions. The test results show that this monitoring system is able to provide information related to temperature data with an accuracy above 98.4%. With this system, users can monitor temperature and humidity based on accumulated data or in real-time so that it is more accurate because it has a small average error of 0.4°C. Users can plan actions to be taken related to controlling environmental conditions.